Need for sustainable architecture - Omer, Spahic (IIUM, 2019)
People are both the creators and demolishers of civilizational accomplishments. They are the only beneficiaries of every great civilizational output. Similarly, people are the conceivers, creators and users of architecture -- a physical locus of civilizations. They create architecture and then use and interact with it. They do so either commendably, securing and enjoying the fruits of their rightful acts so long as they stick to the right systems that led them to such a state, or appallingly with no clear purpose or direction. In the latter’s case, things always work against the authors of and heirs to such an architectural tradition as is anchored in flawed worldviews and value systems, making people’s lives despondent and perilous. Thus, of the essence is that individuals are constantly and painstakingly educated and nurtured. Their progress and involvements should be overseen and monitored along the lines of an adopted proven and genuine worldview, philosophy and vision. In this way, erroneous and unproven worldviews, philosophies and visions can be easily kept at bay and done away with. Their inappropriateness and hazard will always come to the fore whenever contrasted with the recognizable and ubiquitous value and quality of the former. Hence, so important is a state of architecture in the lives of humans that it signifies a microcosm and identity of their cultures and civilizations. It is the people’s third “skin”, their actual skin and clothes being the first and second skin.